The association between sport specialisation and movement competency in youth: a systematic review. Issue 4 (August 2021) - Zoellner, Anja; Whatman, Chris; Read, Paul; Sheerin, Kelly
Negative long-term outcomes have been reported following sport specialisation including increased injury risk. The underlying mechanisms remain unclear; however, fewer exposures to broad ranging movement patterns and reductions in movement competency have been suggested. This review synthesised the evidence to examine if an association is present between sport specialisation and movement competency.  A systematic electronic database search was conducted using combinations of the key words early speciali?ation, sport speciali?ation, early sport speciali?ation, single sport, high school, youth, adolescen *, movement competenc*, movement ability, movement control, movement pattern, physical performance, coordination, fitness, motor skill, motor development, movement performance, neuromuscular control, balance, asymmetr*.  Thirteen articles met the inclusion criteria and were included. Four studies reported no significant differences in movement competency based on specialisation status, while seven showed some measures of movement competency differed but not others. The remaining two studies concluded that adult athletes who participated in two or more sports during high school exhibited better movement competence than those who specialised in a single sport. Multisport athletes commonly displayed improved jump mechanics and performance compared to those competing in a single sport (6/9 studies).  Consistent differences in movement competence based on level of sport specialisation were not shown; however, sport specialisation may result in poorer jump mechanics/performance than playing multiple sports. Further research is needed across a greater range of sports, and consistent definitions of both movement competence and the level of sport specialisation are required to improve our ability to compare and contrast different studies.